Evaluation and Support Mechanisms of an Emerging University-wide Global Health Training Program - Anna Kalbarczyk; Elli Leontsini; Emily Combs; Fan Yang; Azal Ahmadi; Karen Charron (Ubiquity Press, 2016)
Background: Global health education is in high demand in the United States, across the continuum of learning, and field experiences are an essential part of this education. However, evaluations of these programs are limited. Objectives: The aim of this study was to evaluate a field placement program at Johns Hopkins University, in Baltimore, Maryland, to understand how to better support student training overseas and faculty mentorship. Methods: We used qualitative and quantitative methods to gather data from program reporting requirements (152 student surveys and 46 experiential narrative essays), followed by 17 semistructured interviews, and 2 focus groups. Data were analyzed through manual coding and a socioecological model served as an analytical and a synthesizing framework. Findings: A series of factors influence the participants' experience in overseas placements spanning across 4 aggregate levels, from individual to societal, including opportunity for professional advancement, independence, loneliness and illness, mentorship quality, funding, institutional partnership building, opportunity for public health contribution, and for development of cultural competency. Faculty and students thought that the program was beneficial to the learning experience, particularly for its contribution to experiential knowledge of a low- and middle-income country setting and for developing cross-cultural relationships. Communication and scope of work were 2 areas in which students and faculty members often had different expectations and many students emerged having cultivated different skills than they or their mentor initially expected. Students found the experience useful for both their academic and professional careers and faculty members saw mentorship, one of their professional responsibilities, emerge. Conclusions: Many socioecological factors influence an overseas field experience, which in turn produces important effects on students' career choices, and faculty members appreciate the opportunity to serve as mentors. The most vital support mechanisms suggested for faculty and students included available funding, clear preparation, and communication facilitation across the experiential continuum.